СПОСОБЫ ПОВЫШЕНИЯ ЭФФЕКТИВНОСТИ РАБОТЫ ТЕПЛООБМЕННИКОВ (World Science, 2016)
The article describes and shows the heat exchanger to determine the efficiency of heat exchange equipment in which one stream is heated by the use of other heat produced in the process and be cooled. In this study, we calculated the shell and tube heat exchanger.As well as the basic methods of increasing the efficiency of heat exchange equipment in the gas fields.